2003
DOI: 10.21273/horttech.13.1.0035
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Liverwort and Moss Now and in the Future

Abstract: The liverwort, marchantia (Marchantia polymorpha), and silver thread moss (Bryum argenteum) are two highly invasive and difficult to control pests in containerized ornamentals. Container trials were conducted evaluating marchantia and silve r thread moss control with preemergence and postemergence applications of chlorothalonil, captan, ammonium chlorides, hydrogen dioxide, flumioxazin, oxyfluorfen, pelargonic acid, acetic acid (vinegar), copper sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 2 publications
0
30
0
1
Order By: Relevance
“…As profit margins decline and the input costs continually increase, researchers and nursery growers have looked for ways to decrease production costs. From a weed control perspective, this would include many different preventative and sanitation measures, as well as chemical and nonchemical methods of weed control to improve crop growth, reduce economic burden, and increase product marketability (Case et al, 2005;Fausey, 2003).…”
Section: Introduction To Current Weed Control Methodsmentioning
confidence: 99%
“…As profit margins decline and the input costs continually increase, researchers and nursery growers have looked for ways to decrease production costs. From a weed control perspective, this would include many different preventative and sanitation measures, as well as chemical and nonchemical methods of weed control to improve crop growth, reduce economic burden, and increase product marketability (Case et al, 2005;Fausey, 2003).…”
Section: Introduction To Current Weed Control Methodsmentioning
confidence: 99%
“…Wilson and Hughes (1985) reported that oryzalin applied at 9-week intervals provided 99% liverwort control compared with 76% control with oxadiazon applied at a similar frequency. Fausey (2003) reported that flumioxazin sprayed as a 50% water dispersible granule provided 100% pre-emergence liverwort control 35 d after treatment (DAT) and 74% pre-emergence control 60 DAT. In a separate experiment, the same product provided 98% preemergence control 60 DAT, whereas flumioxazin applied as a 0.17% granular provided 95% pre-emergence control 60 DAT (Fausey, 2003).…”
mentioning
confidence: 99%
“…Fausey (2003) reported that flumioxazin sprayed as a 50% water dispersible granule provided 100% pre-emergence liverwort control 35 d after treatment (DAT) and 74% pre-emergence control 60 DAT. In a separate experiment, the same product provided 98% preemergence control 60 DAT, whereas flumioxazin applied as a 0.17% granular provided 95% pre-emergence control 60 DAT (Fausey, 2003). However, none of the aforementioned herbicides are labeled for use in enclosed structures where liverwort pressure is greatest.…”
mentioning
confidence: 99%
“…Silver thread mosses (Bryum argenteum) and liverwort (Marchantia spp.) also can be problematic in container production (Mathers, 2003) and have spread throughout the U.S. nursery industry rather quickly (Fausey, 2003). Both pests are highly invasive and diffi cult to control in containerized ornamentals (Fausey, 2003).…”
Section: Reviewsmentioning
confidence: 99%